Regeneration of Cowpea Vigna radiata L. Plant from Cell Suspension - Al-Qasab, Ghanyah Hiatham; Rasheed, Jamella Hazza (Journal for Research in Applied Sciences and Biotechnology, 2023)
This study dealt with the establishment of cell suspensions culture from cotyledonous stems callus of Vigna radiata L., using an MS medium supplemented with 1.0 mg-1 Naphthalene acetic acid (NAA) and 0.5 mg-1 Benzyl adenine (BA). Two densities of cell suspensions were grown using two types of media. The first medium, MS0, was devoid of growth regulators. The density of the third day was higher than that of the fourth day. The other medium is MS containing growth regulators, and the third-day density was also higher than the fourth-day density in culture suspensions. the cell density grown in MS medium supplemented with growth regulators is higher than the density of cells growing in MS0 medium devoid of growth regulators.